1997
DOI: 10.1136/bjo.81.12.1089
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal laser dacryocystorhinostomy---medium term results

Abstract: Background/aims-Endonasal laser dacryocystorhinostomy (ELDCR) has many potential advantages over conventional external DCR. Although the short term results of this technique have been reported, little is yet known of the long term results, and the occurrence of late rhinostomy failure. The aim of this study was to examine the results at 3 and 12 months following ELDCR. Method-The notes of all consecutiveELDCRs performed between November 1993 and May 1995 were retrieved. Demographic information, details of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 12 publications
1
60
0
3
Order By: Relevance
“…2 EEL-DCR is often performed as day-case surgery under local anaesthesia using the holmium:YAG or the KTP laser. 3,5,7,11,16 Advantages of EEL-DCR over EES-DCR include even less blood loss during surgery and shorter operating time. These advantages make EEL-DCR suitable, for example, for the frail elderly patient, who otherwise might not be fit for longer lacrimal surgery, either under local or under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 EEL-DCR is often performed as day-case surgery under local anaesthesia using the holmium:YAG or the KTP laser. 3,5,7,11,16 Advantages of EEL-DCR over EES-DCR include even less blood loss during surgery and shorter operating time. These advantages make EEL-DCR suitable, for example, for the frail elderly patient, who otherwise might not be fit for longer lacrimal surgery, either under local or under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The perceived disadvantages of the highly successful external approach dacryocystorhinostomy (DCR) [17][18][19][20][21] include the risk of cutaneous scar and lengthy surgery with significant blood loss. These reservations have fuelled the popularity of minimally invasive endonasal approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic laser DCR was first described in cadavers by Massaro et al (1990). Laser DCR (ELDCR) in adults has a 70-80 % success rate (Boush et al 1994;Sadiq et al 1997). The laser is fast, atraumatic, with no sutures and minimal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This is not significantly different from the success rate in adults. A more recent review of 258 external approach DCR's in children under the age of 16 reported a success rate of 96% (Hakin et al 1997) Endoscopic laser DCR has been reported in adults, with success rates of 70-80% (Boush et al 1994;Sadiq et al 1997). There are no reported studies of endoscopic laser DCR in children.…”
mentioning
confidence: 99%